Developing the English Grammar Module Based-Cooperative Learning to Teach Basic English Grammar: Focus on Students’ Needs - Arimuliani Ahmad (Universitas Lancang Kuning, 2018)
Grammar is like a mother of English Language competence which affects all competences in English language proficiency such as speaking, listening, reading and writing. Even though it has been learnt for 9 years by the first semester students’, grammar still becomes a big problem to be mastered. If so, the lecturer should develop epic instructional media based the students’ need and interest to solve this problem. This research is a part of R & D (research and Development) design which only focuses on students’ need analysis. The participant of this research 1B (first semester students) which numbered 38 students. The students are given a questionnaire to be answered to find out the target needs which consist of students’ lack, students’ necessity and the students’ want. This research reveals that results are 76,3% target needs of students (lacks), 76,3% the target needs of students (necessity) and 78,9 % target needs of students (wants).